The utility of procalcitonin in the diagnosis of severe sepsis: a validation study - Naeem, Awais; Asif, Muhammad; Khan, Waleed Rashid; Khan, Aamir; Naz, Saba; Naim, Fahad (International Journal of Pathology, 2025)
Background: One of the main causes of morbidity and death is still severe sepsis, particularly in environments with minimal resources when prompt detection is difficult. Early identification of sepsis may be possible with procalcitonin (PCT), a biomarker that is raised in bacterial infections. By contrasting serum PCT with blood culture data, this study sought to assess the diagnostic accuracy of serum PCT in detecting severe sepsis. Methods: Over the course of six months, from December 1, 2023, to May 1, 2024, this cross-sectional validation study was carried out in the Department of Medicine at Khyber Teaching Hospital in Peshawar. Non-probability consecutive sampling was used to recruit 111 patients with severe sepsis, ages 18 to 60. Blood cultures and serum PCT levels were taken at presentation. All data analysis was performed using SPSS version 25. Patients were determined true positive if both “PCT” (positive procalcitonin) and blood culture were positive; false positive if “PCT” was positive while blood culture was negative; true negative if both “PCT” and blood culture test was negative; and false negative if “PCT” was negative while blood culture was positive. Results: Of the 111 patients, 60.4% were male; the mean age was 42.6 years, the sensitivity of procalcitonin was 87.3%, specificity was 75.0%, positive predictive value was 82.1%, negative predictive value was 81.8%, and overall diagnostic accuracy was 82.0%. There was a statistically significant association between procalcitonin and blood cultures (p = 0.0001). Conclusion: Serum procalcitonin is a valuable diagnostic tool in the early identification of severe sepsis. Procalcitonin’s high sensitivity and strong predictive values lends to a recommendation for the incorporation of serum procalcitonin into clinical practice guidelines for rapid treatment of sepsis.